2017
DOI: 10.1038/s41598-017-00306-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: pNaKtide Attenuates Steatohepatitis and Atherosclerosis by Blocking Na/K-ATPase/ROS Amplification in C57Bl6 and ApoE Knockout Mice Fed a Western Diet

Abstract: We have previously reported that the α1 subunit of sodium potassium adenosine triphosphatase (Na/K-ATPase), acts as a receptor and an amplifier for reactive oxygen species, in addition to its distinct pumping function. On this background, we speculated that blockade of Na/K-ATPase-induced ROS amplification with a specific peptide, pNaKtide, might attenuate the development of steatohepatitis. To test this hypothesis, pNaKtide was administered to a murine model of NASH: the C57Bl6 mouse fed a “western” diet cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 55 publications
2
78
0
Order By: Relevance
“…Chronic obesity and an increase of visceral fat is associated with adipocyte dysfunction that contributes to an increase in reactive oxygen species (ROS) and changes in adipocyte-derived paracrine factors [1], [2], [3]. Obesity-mediated development of hyperglycemia suppresses HO-1 levels [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obesity and an increase of visceral fat is associated with adipocyte dysfunction that contributes to an increase in reactive oxygen species (ROS) and changes in adipocyte-derived paracrine factors [1], [2], [3]. Obesity-mediated development of hyperglycemia suppresses HO-1 levels [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently published studies demonstrated the role of Na/K-ATPase signaling in aggravating oxidative stress and subsequent NASH using in vivo models of a WD diet. These studies extensively illustrated increased hepatic triglycerides levels, hepatic ALT, FFA, FAS and CD36 expression in mice fed a WD diet [9]. This lipid accumulation was confirmed by the histological findings of liver tissues, which exhibited a large number of vacuoles in the liver, significant inflammation and inflammatory cell infiltration into the liver.…”
Section: The Na/k-atpase Oxidant Amplification Loop and Ho-1: Implicamentioning
confidence: 62%
“…The Na/K-ATPase signaling cascade has been extensively studied due to its recently elucidated role as a scaffolding and signaling protein. Studies over the last two decades, since the emergence of the Xie Model of Na/K-ATPase signaling, have demonstrated that activation of this signaling pathway is pivotal in exacerbating oxidative stress in several disease models [8,9,17,18]. While several subunits of Na/K-ATPase have been dissected and known to be involved in its distinct ion pumping function, the α1 subunit of Na/K-ATPase signaling primarily causes its structural modulation leading to the activation of membrane-bound tyrosine kinase protein, Src [19,20].…”
Section: Mechanistic Insights Into Na/k-atpase Oxidant Amplification mentioning
confidence: 99%
See 2 more Smart Citations